Nanotechnology-Based Approaches for the Management of Diabetes Mellitus: An Innovative Solution to Long-Lasting Challenges in Antidiabetic Drug Delivery - Shounak Sarkhel; Saikat Mollick Shuvo; Md Ahesan Ansari; Sourav Mondal; Pritam Kapat; Arindam Ghosh; Tanima Sarkar; Ranu Biswas; Leonard Ionut Atanase; Alexandru Carauleanu (Pharmaceutics)
Diabetes is a widespread metabolic illness. Mismanagement of diabetes can lead to severe complications that tremendously impact patients’ quality of life. The assimilation of nanotechnology in diabetes care holds the potential to revolutionize treatment paradigms, improve patient outcomes, and reduce the economic burden associated with this pervasive disease. This manuscript explores the multifaceted utilization of nanomaterials in diabetes care, emphasizing the unique features of nano-based medication delivery methods and smart drug delivery mechanisms. Additionally, this paper talks about research on nanocarrier-integrated oral, transdermal, and inhalable insulin delivery; dendrimer- and nanocarrier-coupled antisense oligonucleotide-driven gene therapy; the implementation of gold nanoparticles and quantum dots for glucose surveillance; and nucleic acid therapies. There are certain restrictions when using medication delivery methods that are commonly available to handle diabetes. In order to increase efficacy and safety, the rapidly developing science of nanotechnology is also being explored and employed in medical biology. Nanomaterials like liposomes, dendrimers, niosomes, polymeric and metallic nanocarriers, and solid lipid nanoparticles are among the nanocarriers that have been developed for better delivery of various oral hypoglycemic agents in comparison to conventional therapies. These nanocarriers provide great control over elevated blood glucose levels, making them one of the most intriguing and promising technologies available today. Furthermore, adding additional ligands to nanocarriers allows for more focused distribution while protecting the encapsulated hypoglycemic drugs.